Inspired by the "tip effect": a novel structural design strategy for the cathode in advanced lithium–sulfur batteries. Issue 7 (30th January 2017) - Yang, Yuxiang; Wang, Zhenhua; Li, Guangdong; Jiang, Taizhi; Tong, Yujin; Yue, Xinyang; Zhang, Jing; Mao, Zhu; Sun, Wang; Sun, Kening
Abstract : Inspired by the "tip effect", hollow cupric oxide spheres can be used as an effective host for Li–S batteries. Abstract : Inspired by the "tip effect", we demonstrate that hollow cupric oxide spheres (HCOS) built from abundant protrusive crystal strips can be used as an effective host for Li–S batteries. The battery based on this novel host retained an excellent cycle performance over 500 cycles and delivered an improved rate capability.